Practice makes progress: an evaluation of an online scientist–student chat activity in improving scientists' perceived communication skills. Issue 2 (3rd April 2021) - Carroll, Sarah; Grenon, Muriel
Abstract : Scientists are ideally placed to inform, inspire and empower others in science, and thus contribute towards the formation of a scientifically informed society. Despite the increasing emphasis on scientists engaging in Public Engagement in Science, there is not enough structured spaces for scientists to practice. Social-distancing policies incurred by the COVID-19 crisis have forced many PES programmes to move online, incurring further limitations on both training and structured spaces to practice. This pilot study aimed to investigate the impact of participation in four short online training modules and online PES activity on scientists' perceived science communication skills. I'm a Cell EXPLORERS Scientist Online Chat, is a 35-minute text-based chat where young people (aged 11–15 years old) ask questions about science and being a scientist. Both the training and activity were informed by the 'Science Capital Teaching Approach'. The participating scientists ( N  = 11, 8 female and 3 male scientists) comprised a mix of staff and students from four Higher Education Institutions in Ireland. Data were collected via surveys completed after the initial training, directly after each chat, and at the end of the project. Findings indicated that participating in the PES activity increased scientists' perceived proficiency in various science communication skills.